2014
DOI: 10.1111/jnc.12653
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sazetidine‐A maintains anxiolytic effects and slower weight gain following chronic nicotine without maintaining increased density of nicotinic receptors in rodent brain

Abstract: Chronic nicotine administration increases the density of brain a4b2* nicotinic acetylcholine receptors (nAChRs), which may contribute to nicotine addiction by exacerbating withdrawal symptoms associated with smoking cessation. Varenicline, a smoking cessation drug, also increases these receptors in rodent brain. The maintenance of this increase by varenicline as well as nicotine replacement may contribute to the high rate of relapse during the first year after smoking cessation. Recently, we found that sazetid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
(190 reference statements)
0
12
0
Order By: Relevance
“…In contrast, an anxiogenic effect of withdrawal at 24 hours is observed as an increased latency to consume a palatable food in a novel environment when compared to nicotine-treated mice. [28][29][30][31]58 The increased time observed in the BDNF Met/Met mice to initially approach and eat the palatable food during training for the NIH test ( Figure 1B) might be indicative of either increased anxietylike behavior as the food is a novel object introduced into the home cage, or it could be revealing a deficit in training behavior as studies have shown that the BDNF Met/Met mice exhibit impaired spatial and working memory. 59 However, no significant differences between genotype or between treatment groups by the end of training were observed, suggesting that although acquisition of the task was slow, it did not affect the overall performance of these mice on home or novel day.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an anxiogenic effect of withdrawal at 24 hours is observed as an increased latency to consume a palatable food in a novel environment when compared to nicotine-treated mice. [28][29][30][31]58 The increased time observed in the BDNF Met/Met mice to initially approach and eat the palatable food during training for the NIH test ( Figure 1B) might be indicative of either increased anxietylike behavior as the food is a novel object introduced into the home cage, or it could be revealing a deficit in training behavior as studies have shown that the BDNF Met/Met mice exhibit impaired spatial and working memory. 59 However, no significant differences between genotype or between treatment groups by the end of training were observed, suggesting that although acquisition of the task was slow, it did not affect the overall performance of these mice on home or novel day.…”
Section: Discussionmentioning
confidence: 99%
“…However, varenicline also exhibits activity at additional nAChR subtypes, including α3β4*-nAChR and α7-nAChR (Grady, Drenan et al 2010, Papke, Wecker et al 2010, Campling, Kuryatov et al 2013). Studies using rodent and cell culture models to evaluate the effects of chronic varenicline exposure have demonstrated that, similar to nicotine, these treatments elicit an up-regulation of α4β2*-nAChR binding sites (Turner, Castellano et al 2011, Hussmann, Turner et al 2012, Hussmann, DeDominicis et al 2014). In humans, at therapeutic doses, varenicline may have effects on nAChRs other than β2* (Campling, Kuryatov et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently unknown whether changes in nAChR expression are maintained by all smoking cessation treatments, although some compounds under investigation appear to allow return to baseline for α4β2*-nAChR (Turner, Castellano et al 2010, Hussmann, Turner et al 2012, Hussmann, DeDominicis et al 2014, Yohn, Turner et al 2014). Whether reversal of these changes is an important aspect of a successful quit attempt is also not known.…”
Section: Introductionmentioning
confidence: 99%
“…Replacement of nicotine with chronic administration of Saz-A, a potent nAChR partial agonist (Xiao, Fan et al 2006) that causes desensitization of α4β2 nAChRs, was shown to reverse the upregulation of the receptor induced by chronic nicotine administration. Besides, this drug, like nicotine, was able to reduce body weight in rats (Hussmann, DeDominicis et al 2014). Therefore, it may be that weight-reducing effect of nicotine is mediated, at least in part, by its action on POMC neurons via the α4β2 nAChRs.…”
Section: Introductionmentioning
confidence: 99%